Cost analyses approaches in medical education: there are no simple solutions. Issue 10 (9th September 2013) - Walsh, Kieran; Levin, Henry; Jaye, Peter; Gazzard, James
Abstract : Context: Medical education is expensive. Although we have made progress in working out 'what works' in medical education, there are few data on whether medical education offers value relative to cost. Research into cost and value in medical education is beset by problems. One of the major problems is the lack of clear definitions for many of the terms commonly used. Phrases such as cost‐effectiveness analysis, cost‐benefit analysis, cost‐utility analysis and cost‐feasibility analysis are used without authors explaining to readers what they mean (and sometimes without authors themselves understanding what they mean). Sometimes such terms are used interchangeably and sometimes they are used as rhetorical devices without any real evidence that backs up such rhetoric as to the cost‐effectiveness or otherwise of educational interventions. The frequent misuse of these terms is surprising considering the importance of the topics under consideration and the need for precision in many aspects of medical education. Methods: Here we define commonly used terms in cost analyses and give examples of their usage in the context of medical education. Conclusions: Cost‐effectiveness analysis refers to the evaluation of two or more alternative educational approaches or interventions according to their costs and their effects in producing a certain outcome. Cost‐benefit analysis refers to 'the evaluation of alternatives according to their costs and benefits when each is measured in monetary terms'. Cost‐utility analysis is the examination of two or more alternatives according to their cost and their utility. In this context, utility means the satisfaction among individuals as a result of one or more outcome or the perceived value of the expected outcomes to a particular constituency. Cost‐feasibility analysis involves simply measuring the cost of a proposed intervention in order to decide whether it is feasible. Abstract : Discuss ideas arising from the article at 'discuss'